Educational environment of shaping conflict resolution skills at the tertiary level - Holubnycha, Liudmyla; Sytnykova, Yuliia; Shchokina, Tetiana; Soroka, Natalia; Demchenko, Dina; Malieieva, Tetiana (Institute of Advanced Engineering and Science, 2025)
As the modern world is characterized by a large number of various conflicts, it is vital for people to resolve them peacefully. So, it is relevant to develop conflict resolution skills while educating students. The research aimed to examine how certain educational environments designed to cultivate conflict resolution skills in students influence the development of these skills level. A total of 139 students of a Ukrainian university, consisted of two experimental group (E1=48; E2=46) and a control group (C=45) participated in the experiment and produced significant findings that are crucial to the field of conflict resolution skills development. The χ² test helped analyses the experiment data and make a conclusion about its statistical significance. The p-value (less than 0.05) indicated that the difference between the experimental and control groups was statistically significant at the 0.05 level of significance. Results revealed that the students of the experimental groups had substantially higher achievements than the control group students. Thus, educational environments designed to cultivate conflict resolution skills effectively influence these skills level development if academic staff purposefully promotes it. It is recommended to utilize the proposed educational environments in complex within formal educational settings, during extracurricular activities and internships.